Strategic and tactical electronic business solutions in pharmacies and drug stores. (1st January 2013) - Duncan, Jonathon; Wei, June; Liu, Manlu
The purpose of this paper is to develop electronic service solution standards in the pharmacies and drug stores strategically and tactically. Specifically, it first developed a strategic value chain model to present the adoptions of information and communication technologies in the pharmacies and drug stores for business value increases. Second, a set of tactical electronic business standards were in the pharmacies and drug stores. Third, the implementation patterns of the top 20 dominant companies in the pharmacies and drug stores were analysed. The results of this research will help to accelerate the adoption of information and communications technologies in the pharmacies and drug stores to achieve value increase in business. The managerial and practical implications were also presented.